Pulmonary hypertension due to lung diseases: Updated recommendations from the Cologne Consensus Conference 2018. (1st December 2018) - Olschewski, Horst; Behr, Jürgen; Bremer, Hinrich; Claussen, Martin; Douschan, Philipp; Halank, Michael; Held, Matthias; Hoeper, Marius M.; Holt, Stephan; Klose, Hans; Krüger, Stephan; Lange, Tobias J.; et al.
Abstract: The 2015 European Guidelines on Pulmonary Hypertension did not only cover pulmonary arterial hypertension (PAH) but also some aspects of pulmonary hypertension (PH) associated with chronic lung disease. The European Guidelines point out that the drugs currently used to treat patients with PAH (prostanoids, endothelin receptor antagonists, phosphodiesterase‑5 inhibitors, sGC stimulators) have not been sufficiently investigated in other forms of PH. Therefore, the European Guidelines do not recommend the use of these drugs in patients with chronic lung disease and PH. This recommendation, however, is not always in agreement with medical ethics as physicians sometimes feel inclined to treat other forms of PH which may affect quality of life and survival of these patients in a similar manner. To this end, it is crucial to consider the severity of both PH and the underlying lung disease. In June 2016, a Consensus Conference organized by the PH working groups of the German Society of Cardiology (DGK), the German Society of Respiratory Medicine (DGP) and the German Society of Paediatric Cardiology (DGPK) was held in Cologne, Germany, to discuss open and controversial issues surrounding the practical implementation of the European Guidelines. Several working groups were created, one of which was dedicated to the diagnosis and treatment of PH in patients with chronic lung disease. The 2018 updated recommendations of this working group are summarized in the present paper.